2012
DOI: 10.1002/ptr.4713
|View full text |Cite
|
Sign up to set email alerts
|

S‐Allylcysteine, a Garlic Compound, Increases ABCA1 Expression in Human THP‐1 Macrophages

Abstract: ATP-binding cassette transporter A1 (ABCA1) is a key mediator of cholesterol efflux to apoA-I in lipid-loaded macrophages, which is the first step of reverse cholesterol transport in vivo and a critical step in preventing atherosclerosis. Enhanced ABCA1 expression may inhibit foam cell formation and consequently reduce atherogenic risk. The purpose of this study was to investigate the effect of S-allylcysteine (SAC), the most abundant organosulfur compound in aged garlic extract, on the expression of ATP-bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Similarly, various proteasome inhibitors and ApoA1, an acceptor of cholesterol transferred by ABCA1, restore cholesterol efflux in macrophages by suppression of ABCA1 degradation . S‐allylcysteine, a major garlic extract constituent, possesses the atheroprotective activity by increasing ABCA1 expression through unknown mechanism . However, lipid‐lowering properties of S‐allylcysteine appear to play a secondary role in a summary of its anti‐atherogenic effects as this cysteine derivative only moderately inhibited lipid accumulation in macrophages .…”
Section: Cholesterol Effluxmentioning
confidence: 99%
“…Similarly, various proteasome inhibitors and ApoA1, an acceptor of cholesterol transferred by ABCA1, restore cholesterol efflux in macrophages by suppression of ABCA1 degradation . S‐allylcysteine, a major garlic extract constituent, possesses the atheroprotective activity by increasing ABCA1 expression through unknown mechanism . However, lipid‐lowering properties of S‐allylcysteine appear to play a secondary role in a summary of its anti‐atherogenic effects as this cysteine derivative only moderately inhibited lipid accumulation in macrophages .…”
Section: Cholesterol Effluxmentioning
confidence: 99%
“…Toll-like receptor 2 agonist Pam(3)CSK(4) upregulated ABCA1 gene expression in RAW 264.7 macrophages via the activation of the PKCη/phospholipase D2 signaling pathway (Park et al 2013). S-Allylcysteine, the most abundant organosulfur compound in aged garlic extract, also elevated ABCA1 content in human THP-1 macrophages (Malekpour-Dehkordi et al 2013). The data showed that stimulation with CXCL5 that has a protective role in atherosclerosis (Rousselle et al 2013) induced ABCA1 expression in alternatively activated (M2) macrophages but not in classically activated (M1) macrophages.…”
Section: Upregulatory Mechanisms Of Abca1 Gene Expressionmentioning
confidence: 99%
“…Garlic has been used as a home remedy for a myriad of diseases for thousands of years. To date, garlic and its constituents are known to have many beneficial attributes such as antimicrobial (Casella et al, 2013;Goncagul and Ayaz, 2010), antiatherosclerotic (Asdaq et al, 2009;Chan et al, 2013;Gonen et al, 2005;Malekpour-Dehkordi et al, 2013), antitumorigenetic (Iciek et al, 2009;Kaschula et al, 2011), and immunomodulatory (Iciek et al, 2009) properties. Of particular interest for our studies is the modulation of cytokine production by garlic as cytokines are important immune system mediators.…”
Section: Introductionmentioning
confidence: 99%